2022
DOI: 10.3390/plants11060747
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and Diverse Transcriptional Reprogramming Triggered by the Establishment of Symbioses in Tomato Roots Forming Arum-Type and Paris-Type Arbuscular Mycorrhizae

Abstract: Arbuscular mycorrhizal (AM) fungi allocate mineral nutrients to their host plants, and the hosts supply carbohydrates and lipids to the fungal symbionts in return. The morphotypes of intraradical hyphae are primarily determined on the plant side into Arum- and Paris-type AMs. As an exception, Solanum lycopersicum (tomato) forms both types of AMs depending on the fungal species. Previously, we have shown the existence of diverse regulatory mechanisms in Arum- and Paris-type AM symbioses in response to gibberell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The representative enriched pathways include transmembrane transport, regulation of protein kinase activity, fatty acid biosynthesis, fatty acid metabolic process, brassinosteroid homeostasis, response to peptide hormone, and ammonium transmembrane transport ( Figure 2 C). These pathways are highly consistent with those reported by previous studies on AMS using tomato and other angiosperms as host plants ( Sugimura and Saito, 2017 ; Tominaga et al., 2021 , 2022 ; Vasan et al., 2021 ).
Figure 2 Identification of the upregulated tomato protein-coding genes between AIR and ANR samples.
…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The representative enriched pathways include transmembrane transport, regulation of protein kinase activity, fatty acid biosynthesis, fatty acid metabolic process, brassinosteroid homeostasis, response to peptide hormone, and ammonium transmembrane transport ( Figure 2 C). These pathways are highly consistent with those reported by previous studies on AMS using tomato and other angiosperms as host plants ( Sugimura and Saito, 2017 ; Tominaga et al., 2021 , 2022 ; Vasan et al., 2021 ).
Figure 2 Identification of the upregulated tomato protein-coding genes between AIR and ANR samples.
…”
Section: Resultssupporting
confidence: 92%
“…Among the upregulated genes (defined as AMS-induced genes hereafter), 28 were orthologous to those known to be involved in AMS, including PT4 , RAM1 , RAD1 , FatM , and STR , along with some additional AMS-associated genes, demonstrating the AIRs were well colonized by AMF ( Supplemental Figure 2 and Supplemental Table 2 ). Using data from three previously reported tomato AMS-associated transcriptome studies ( Sugimura and Saito, 2017 ; Ho-Plagaro et al., 2019 ; Tominaga et al., 2022 ), a comparative analysis with AMS-induced genes was performed. The results showed that a set of 280 AMS-induced genes was identified in all four data sets; 193 and 703 genes were shared by three and two studies, respectively ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…STs are key signaling molecules used by plants to attract AMF through interactions with other phytohormones ( Lanfranco et al., 2018 ; Faizan et al., 2020 ). GAs specific roles in AMF colonization and AM symbiosis are still unclear and confusing ( Takeda et al., 2015 ; Tominaga et al., 2020 ; Tominaga et al., 2021 ; Tominaga et al., 2022 ). According to these studies, GA may promote or alter AMF penetration and proliferation in plants’ roots depending on the type of fungi.…”
Section: Discussionmentioning
confidence: 99%